Meningkatkan Kemampuan Mengenal Konsep Bilangan 1-10 Melalui Media Puzzle Bagi Siswa (Classroom Action Research kelas III C SDLBN 127710 Pematang Siantar) - Monika Evalina Siregar; Iga Setia Utami (Jurnal Penelitian Pendidikan Khusus, 2023)
The purpose of this article is to find information on increasing conceptual ability through puzzle media for students in Class III of Mild Intellectual Disability, SLBN 127710 Pematang Siantar. The survey was conducted from July to August 2022. This research method is classroom action research. This research he divided into two cycles. The study subjects consisted of three of her students with mild intellectual disabilities. As a result, the expected skill maturity exceeded the prescribed score of 65. Therefore, this study was completed in just two cycles. Thus, it can be concluded that media puzzles can improve number concept skills in children with mild intellectual disability.